Evaluación de los Procesos Socioeconómicos del Uso y Ocupación del Territorio en la Provincia de Picota, Departamento de San Martín. 2012 - Torres D., Jorge (2014)
The research “socioeconomic process and setting of territory evaluation in the province of Picota, Department of San Martín. 2012” has been executed with the purpose of evaluating the socioeconomic processes and of identifying the reasons that motivated the use and occupation of the territory. At the same time the purpose is to determine the zones of the current use generated by the anthropic activities processes and conditions that allowed to elaborate a database from field exists to ten districts of the Provinceswith the geographical application of information systems. For the visual analysis, one used the satellite images Landsat TM-5-2005, 2007 and 2099, likewise one used other sources of primary information for the identification and evaluation of activities. The reasons of the use and territory occupation identified are: Alternative cultures production, terrorism and drug dealing, international market trends and weak land management. Currently the main use zone in the province of Pillory are: Productive sources ofpredominance of Rice, Corn, Coffee, Cocoa, Papaya, Coconut, Pine kernel, Tobacco, Soy, Sorghum, Cattle raising, diversified Agriculture, Secondary and Primary Forest, Urban use and Waterbody that represent 100% (206 143.093 Ha).